THE EFFECTIVENESS OF ENGLISH TALKING BOOK IN TEACHING READING AT THE EIGHTH GRADE OF JUNIOR HIGH SCHOOL - Hartini, Nurani (ELT Perspective Jurnal Pendidikan Bahasa Inggris, 2014)
ABSTRACT This research entitledâThe Effectiveness of English Talking Book in Teaching Reading at The Eighth Grade of Junior High Schoolâ. The researcher aims to investigate whether the English Talking Book in Teaching Reading at the Eighth Grade of Junior High School effective in Reading Aloud.Theories used to support this research are from Patel and Jain (2008) about the audio visual media and reading aloud.Audiovisual media involves more than one sensory organs of the learner which improves retentiveness and makes learning permanent also seeing and hearing go together which play ordinary roles in learning. Meanwhile, reading aloud is very important for the teacher to carry out, to know, and to check the studentsâ pronunciation, information, stress, paused, and rhythm and their ability in various short of punctuation marks.The research used experimental research of method, and took two classes consisting of 30 students each class as sample in SMP Al WashliyahSumber. The data for this experimental study were studentsâ reading scores, and the reading scores were analyzed of using McMillan and Schumacherâs formula. The research found that the reading scores of the experimental group is higher than the control group. The result of t account is 0.75, t table is 1,672 for Î± = 5%it means that t account is higher than t table (t account> t table). Therefore, the conclusion is English Talking Book in Teaching Reading at the Eighth Grade of Junior High School is effective in Reading Aloud.English Talking Book in teaching reading makes the students enthusiasm to learn the fairy tale text and help them produce correct intonation or tunes and notice how English is spoken differently from the way they are written and listen very well. It is suggested to use of English Talking Books in Teaching Reading as an alternative media in order to studentsâ ability in Reading Aloud other genres of texts or to improve studentsâ listening skill. Keywords :English Talking Book, Reading Aloud, Fairy Tale Text